Windsor Castle - Bennington, Clara (Minneapolis, MN Jump!, Inc., 2020)
"In this book, early fluent readers will learn about the history, location, many rooms, and uses of Windsor Castle. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn more about Windsor Castle and its cultural history."--Provided by publisher.
A castle in Windsor -- Fire in the castle! -- Around castle grounds -- Quick facts & tools -- At a glance -- Glossary.
Includes index.
560L
Ages 7-10.
107611
Keywords: Windsor Castle -- England; Great Britain -- Kings and rulers -- Dwellings -- Juvenile literature; Windsor Castle; Juvenile works